2012
DOI: 10.4103/0255-0857.103771
|View full text |Cite
|
Sign up to set email alerts
|

16S rDNA-based metagenomic analysis of human oral plaque microbiota in patients with atherosclerosis and healthy controls

Abstract: To address the question if an altered oral microbiota is associated with atherosclerosis. Twenty patients suffering from atherosclerosis and 10 controls were recruited. Clinical oral, medical and laboratory investigations were performed. Oral bacteria were collected and 16S rDNA was sequenced following Single strand conformation polymorphism.(SSCP) Probing pocket depths in patients were significantly elevated. The oral microbiota of patients and controls were dominated by Fusobacterium (16%/17%), Streptococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…For these genera, no significant difference was found between both groups. These bacterial genera were also reported with the highest relative abundances in the oral microbiota of coronary patients and controls in the previous studies [ 12 , 13 ]. Streptococcus and Veillonella are early colonizers during the process of biofilm formation in the oral cavity initiated by the aggregation of these bacteria to establish an initial microenvironment [ 8 ].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…For these genera, no significant difference was found between both groups. These bacterial genera were also reported with the highest relative abundances in the oral microbiota of coronary patients and controls in the previous studies [ 12 , 13 ]. Streptococcus and Veillonella are early colonizers during the process of biofilm formation in the oral cavity initiated by the aggregation of these bacteria to establish an initial microenvironment [ 8 ].…”
Section: Discussionsupporting
confidence: 69%
“…In the previous studies, while abundance of Anaeroglobus in the oral cavity was associated with symptomatic atherosclerosis [ 12 ], CAD was not related to significant qualitative changes of the oral microbiota compared with healthy controls in other studies [ 11 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Considering the potential role of inflammation during periodontitis in escalating artherosclerosis, it is important to obtain the oral health status of subjects while deciphering this link. None of the studies, except Ismail et al (2012), reported oral health data to stratify the population into study or control groups. Moreover, one of the studies has not taken oral samples and inferences were drawn based solely on the identification of the taxa in the artherosclerotic plaque (Calandrini et al 2014).…”
Section: Oral Microbiome and Atherosclerosismentioning
confidence: 99%